Tempe Kedelai (Rhizopus oligosporus) sebagai Alternatif Anti Inflamasi - Athiyya Husna; Emriadi Emriadi; Bambang Ristiono (Andalas Dental Journal, 2021)
Background: Inflammation is a protective mechanism of the immune system due to tissue damage caused by infectious and non infectious agents. The most widely used synthetic drugs in treating the inflammation is NSAIDs (Non Steroidal Anti Inflammatory Drugs) but long-term use of NSAIDs can cause undesirable side effects. Tempeh (R. oligosporus) is one of the processed soy products that is made through the fermentation process by Rhizopus sp. Tempeh has many benefits for health, one of which is anti-inflammatory. According to some research results, tempeh is recognized as having an anti-inflammatory role. The mechanism of tempeh as an anti-inflammatory, namely by maintain a balance between reactive oxygen species (ROS) and antioxidants in the body, increasing the production of anti-inflammatory cytokines (IL-10), suppressing the activation of NF-kB. This process can suppress the expression of iNOS and COX-2 and inhibit several inflammatory mediators, such as TNF-α, IL-1β and NO. Objective: The purpose of this study was to investigate anti-inflammatory activity of soybean tempeh (R.oligosporus) and find out the potential of active compounds in soybean tempeh that play role as anti-inflammatory. Method: The study was conducted by collecting and examining of various literatures on potential of soybean tempeh (R.oligosporus) in suppressing inflammatory response. Conclusion: The active compounds found in soybean tempeh (R. oligosporus) is able to suppress the inflammatory response.